Crystalline boragermenes - Rao, Bin (2022)
Boragermene 3 featuring a double bond between the Ge and dicoordinate B atoms has been synthesized for the first time by reacting the cyclic (alkyl)(boryl)germylene-PMe3 adduct 1 with Cl2 BN(SiMe3 )2 followed by reductive dehalogenation with KC8 . Addition of a Lewis base (Me NHC) to 3 leads to the formation of the corresponding adduct 4, which shows double bond character between the Ge and tricoordinate B atoms. Compound 3 undergoes hydrogenation with H2 concomitant with a complete scission of the Ge=B bond.